An atlas of the commoner skin diseases : with 153 plates reproduced by direct colour photography from the living subject - Semon, Henry C. (Henry Charles), 1881-; Wilson, Harold T. H. (John Wright & Sons Ltd., 1957)
An Atlas of the Commoner Skin Diseases focuses on dermatoses most frequently observed in the routine outpatient practice. The book provides abbreviated clinical descriptions, diagnosis, and prognosis, as well as outline of treatment. The book first offers information on the differential diagnosis and treatment of acne and its variants, alopecia areata, cellulitis, cheiropompholyx, and chilblains. The text also ponders on the diagnosis, treatment, and prophylaxis of dermatitis and its variants. The publication also takes a look at the treatment, antihistaminic agents, and psychotherapy of ecze.